Management Plan to Appreciate and Understand Thailand's Heritage Case study: Prasat Phimai, Nakhon Ratchasima Province, Thailand - Maneenetr, ์Nartradee (Journal of Business, Innovation and Sustainability (JBIS), 2006)
Download DOI: http://dx.doi.org/10.14456/becj.2006.9